2023
DOI: 10.1021/acs.macromol.3c00396
|View full text |Cite
|
Sign up to set email alerts
|

Effective Fermi-Level Modulation of Two-Dimensional Conjugated Covalent Organic Frameworks Achieved by Introducing p-Type Organic Dopants

Abstract: Covalent organic frameworks (COFs) are a new emerging class of two-dimensional functional materials, and their unique electronic character plays a key role in practical applications. Here, to provide a useful strategy to tune the electronic character of COFs, doping effects with organic molecular acceptors, TCNQ, F4TCNQ, and TCNE, on the frontier orbital energy levels of sp2c-COF and COF366 mono- and bilayers are explored. Due to the charge transfer from COFs to dopants, the Fermi level is shifted to a lower e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…32 However, it is generally accepted that the relative laws and trends are reliable under the same calculation method. 33,34 Considering electron transition energies are mainly dominated by the frontier energy bands, density of states projected (PDOS) onto different atom types involved in C 12 H 28 NCuCl 2 and C 20 H 48 N 2 Cu 4 Cl 6 were analyzed and shown in Figures 3g and 3h. Further frontier energy band diagram was constructed based on the PDOS and BS results to illustrate their luminescence mechanism, as presented in Figures 3i and 3j.…”
Section: Mitzi Et Al Have Prepared High-quality Thin Films Via Meltingmentioning
confidence: 99%
See 1 more Smart Citation
“…32 However, it is generally accepted that the relative laws and trends are reliable under the same calculation method. 33,34 Considering electron transition energies are mainly dominated by the frontier energy bands, density of states projected (PDOS) onto different atom types involved in C 12 H 28 NCuCl 2 and C 20 H 48 N 2 Cu 4 Cl 6 were analyzed and shown in Figures 3g and 3h. Further frontier energy band diagram was constructed based on the PDOS and BS results to illustrate their luminescence mechanism, as presented in Figures 3i and 3j.…”
Section: Mitzi Et Al Have Prepared High-quality Thin Films Via Meltingmentioning
confidence: 99%
“…It is because the high-frequency exchange function is not introduced in the standard DFT-PBE level, which is likely to underestimate absolute VBM–CBM energy gaps . However, it is generally accepted that the relative laws and trends are reliable under the same calculation method. , …”
mentioning
confidence: 99%
“…Considering the standard DFT-PBE level tends to underestimate absolute VBM-CBM energy gaps, the electronic structures of pristine BiVO 4 and F-doped BiVO 4 were calculated by more accurate range-separated Heyd–Scuseria–Ernzerhof (HSE) hybridization functions, 43,44 for which the screening parameter was set to 0.2 Å −1 and the Hartree–Fock mixing parameter was set to α = 0.15. Considering it is generally accepted that the relative laws and trends, such as relative energy level shifts, are reliable under the same calculation method, 45 the energy level of alignment of pristine BiVO 4 and F-doped BiVO 4 was also examined by PBE functional for comparison.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Surface modification is an effective one, since it can affect molecular adsorption and catalytic behavior through introducing impurity levels near the Fermi energy. 8–10 For example, Fan et al reported that the d-orbital of doped transition metal (TM) atoms plays an important role in activating MoS 2 to adsorb gas molecules. 11 Similarly, non-metals can also induce gap states as reported by Yang et al For example, they confirmed that N–In 2 O 3 generates a mid-gap energy state, reduces the band gap of the photocatalyst, and improves solar energy utilization, which has a highly selectivity of CO 2 reduction to methanol.…”
Section: Introductionmentioning
confidence: 99%